INFORMATION PROCESSING DEVICE, INFORMATION PROCESSING METHOD AND PROGRAM - OGAWA TETSU; TAKASHIMA MASATOSHI (2019)
The purpose of the present invention is to obtain an image for which there are few errors in the composite information of, for example, a composite image. In order to achieve the foregoing, the present invention extracts, for an acquisition image including information of a specific wavelength region, an image of a specific region, which is a specific positional range within an image, for example,and generates composite information by synthesizing the information of a plurality of specific regions extracted respectively from a plurality of imaging information items captured at different time points. By carrying out the foregoing on captured images captured while moving and at each time point, composite information with few errors can be obtained for a wide-range of subjects. 本发明的目的在于获得这样的图像：针对该图像，在例如合成图像的合成信息中存在很少误差。为了实现前面的目的，本发明针对包括特定波长区域的信息的获取图像提取例如作为图像内的特定位置范围的特定区域的图像，并且通过合成分别从在不同时间捕获的多个成像信息项提取的多个特定区域的信息来产生合成信息。通过对在移动的同时并且在每个时间点捕获的捕获图像执行前面的操作，能够针对宽范围的被摄体获得具有很少误差的合成信息。